Utilization pattern of child health care services in the rural area of Surendranagar district: a community based cross sectional study - Vachhani, Pushti V.; Bhimani, Nishant R.; Sutaria, Nishith B.; Kartha, Girija P. (International Journal of Research in Medical Sciences, 2017)
Background: Infant and child mortality continues to be a major public health problem all over the country. Despite the existence of national programmes for improving child health in India, child mortality and morbidity continue to be high. Utilization of child health care services is poor in the rural areas, causing significant impact on the health causing increased morbidity and mortality. Methods: It was a Community based Cross-sectional study carried out in the rural area of Surendranagar district through oral questionnaire method which was pre-designed and pretested. Data on demography, history of colostrum, initiation of breastfeeding, prelacteal feeds, exclusive breastfeeding, introduction of complementary feeding, immunization, respiratory infections etc. were collected, compiled and analyzed by applying appropriate tests using SPSS. Results: Out of 154 participants, 43.51% were offered breastfeeding within one hour of birth. Association was observed between initiation of breastfeeding, exclusive breastfeeding, time of introduction of complementary foods and duration of breastfeeding and utilization of health education services. Educational level of mothers and immunization status of the children had a significant statistical association. The overall prevalence of ARI was 31.82% & of Diarrhoea was 39.61%. Conclusions: A positive association was observed between nutritional status and utilization of nutritional services. Significant impact of health education services given during the antenatal period was observed on initiation of breastfeeding as well as exclusive breastfeeding. Although child services in India have been created, strengthened and expanded over the years, their performance in terms of utilization particularly in rural area is still limited.